Dynamically tunable perfect absorption based on the phase transition of vanadium dioxide with aluminum hole arrays. (February 2019) - Zhou, Peng; Zheng, Gaige; Chen, Yunyun; Xu, Linhua; Xian, Fenglin
Abstract: Integrating plasmonic nanostructures with functional materials can further control over the optical resonant responses. A perfect absorber (PA) consisting of aluminum (Al) ring array intercalated with vanadium dioxide (VO2 ) disk is presented. The resonance wavelength of absorption peak can be tuned over a wide range in the visible (Vis) and near-infrared (NIR) regimes. The absorption peak shifts from 770 nm to 1336 nm while VO2 undergoes a structural transition from metallic phase (m-VO2 ) to insulator phase (i-VO2 ), resulting in a relative 73.5% wavelength shift. In addition, the absorption peak is strongly dependent on the height and radius of the ring disk as well as the period of lattice. Our work also suggests that the designed VO2 -based absorber has the potential to overcome the difficulty in performing dynamically tunable resonances and near-unity absorbance with wide angle of incidence as well as weak polarization dependence. Highlights: A perfect absorber consisting of aluminum ring array intercalated with vanadium dioxide disk is presented. The absorption peak shifts while VO2 undergoes a structural transition from metallic to insulator phase. The design exhibits strong electromagnetic field concentration. The absorber shows high absorptive performance independent of the incident angle and polarization.